A case of anti‐melanoma differentiation‐associated gene 5 antibody‐positive dermatomyositis‐associated rapidly progressive interstitial lung diseases developed after administration of COVID‐19 vaccine and subsequent pneumococcal vaccine. Issue 12 (2nd November 2022) - Takahashi, Saeko; Kato, Ai; Hashimoto, Kanako; Takehara, Tomohiro; Ishioka, Kota; Takanashi, Satoshi
Abstract: Five cases of anti‐melanoma differentiation‐associated gene 5 antibody‐positive dermatomyositis‐associated rapidly progressive interstitial lung diseases (anti‐MDA5‐positive DM‐RPILD) following COVID‐19 vaccination have been reported previously. We present the first case of the disease that developed following the sequence of COVID‐19 infection, COVID‐19 vaccination, and 23‐valent pneumococcal polysaccharide vaccine (PPSV23) administration. A 75‐year‐old‐Japanese man received the third dose of Pfizer COVID‐19 vaccine 4 weeks after he had a mild COVID‐19 infection. Eleven weeks after vaccination, he received PPSV23 for the first time. He developed fever, malaise, and anorexia the day after the PPSV23, rash a week later, and shortness of breath 2 weeks later. He was then admitted to a local hospital and treated with antibiotics, but his condition worsened. He was transferred to our hospital 4 weeks after the PPSV23 and was diagnosed with anti‐MDA5‐positive DM‐RPILD. Despite intensive treatment, the patient died on the 10th hospital day. Abstract : Five cases of anti‐melanoma differentiation‐associated gene 5 antibody‐positive dermatomyositis‐associated rapidly progressive interstitial lung diseases (anti‐MDA5‐positive DM‐RPILD) following COVID‐19 vaccination have been reported previously. We present the first case of the disease that developed following the sequence of COVID‐19 infection, COVID‐19 vaccination, and 23‐valent pneumococcal polysaccharide vaccine (PPSV23) administration.